Autologous fibrin glue as an encapsulating scaffold for delivery of retinal progenitor cells - Ahmed, Tamer A.; Ringuette, Randy; Wallace, Valerie A.; Griffith, May (Frontiers in Bioengineering and Biotechnology, 2015)
The retina is a highly sophisticated piece of the neural machinery that begins the translation of incoming light signals into meaningful visual information. Several degenerative diseases of the retina are characterized by photoreceptor loss and eventually lead to irreversible blindness. Regenerative medicine, using tissue engineering-based constructs to deliver progenitor cells or photoreceptors along with supporting carrier matrix is a promising approach for restoration of structure and function. Fresh fibrin glue (FG) produced by the CryoSeal®FS system in combination with mouse retinal progenitor cells (RPCs) were evaluated in this study. In vitro expanded RPCs isolated from postnatal mouse retina were encapsulated into FG and cultured in the presence of the protease inhibitor, tranexamic acid. Encapsulation of RPCs into FG did not show adverse effects on cell proliferation or cell survival. RPCs exhibited fibroblast-like morphology concomitantly with attachment to the encapsulating FG surface. They expressed α7 and β3 integrin subunits that could mediate attachment to fibrin matrix via an RGD independent mechanism. The three dimensional environment and the attachment surface provided by FG was associated with a rapid downregulation of the progenitor marker SOX2 and enhanced the expression of the differentiation markers CRX and recoverin. However, the in vitro culture conditions did not promote full differentiation into mature photoreceptors. Nevertheless, we have shown that autologous fibrin, when fabricated into a scaffold for RPCs for delivery to the retina, provides the cells with external cues that could potentially improve the differentiation events. Hence, transient encapsulation of RPCs into FG could be a valid and potential treatment strategy to promote retinal regeneration following degenerative diseases. However, further optimization is necessary to maximize the outcomes in terms of mature photoreceptors.